Truth Claims and Multicultural Values in Learning Religious Education - Rohmah, Siti; Mamonto, Merdi F.; Wahid, Abdul; Solong, Najamuddin Petta; Mokodenseho, Sabil (Letiges, 2023)
This study analyses truth claims and multicultural values made by school teachers. This research is necessary because schools have teachers and students with different cultural, customs and religious backgrounds. These differences sometimes become obstacles to creating harmony in schools. Misunderstandings, especially in understanding religion due to students' ignorance, have triggered disputes in association at school. This type of research is field research using exploratory qualitative methods. At the same time, the research approach uses sociological-anthropological and structural-functional. This study uses primary data from interview results, while books, journal articles, and relevant literature are used as secondary data. Research data were collected using non-participant observation techniques, structured interviews, and documentation. The research objects were school principals, teachers of Islam, Christianity and Hinduism, and Muslim, Christian and Hindu students. The collected data were analyzed inductively. This study found that teachers in schools are still at the level of understanding of pluralism in religion and tend to be tolerant but have yet to implement multicultural values profoundly and equitably in schools. In addition, learning the doctrine of religious truth is in synergy with multicultural understanding in interfaith in the school environment. However, it is still applying an attitude of tolerance between religious communities. This research contributes to cultivating students' pluralist attitudes by mapping the pluralist attitudes of pro-anticipation students before conflicts occur in multicultural societies in religious education learning.